Study of umbilical coiling index and perinatal outcome - Singh, Sujata; Pai, Swati; Sahu, Barsha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Study was to evaluate the relationship between umbilical coiling index (UCI) and hypo-and hyper coiling of the umbilical cord and parity, neonatal weight, Ponderal Index (PI), APGAR (Appearance, pulse, grimace, activity, and respiration) score, meconium staining of the amniotic fluid, Intrauterine growth restriction (IUGR), hypertensive disorders of pregnancy and delivery interventions. Method: A prospective analytical study was performed from January 2017 to December 2018. Total of 300 patients giving birth at labour room of SCB Medical College, Cuttack were taken into study. Immediately following delivery, the umbilical cord was clamped at the foetal end and cut with scissors. UCI, mode of delivery and perinatal outcome was followed up. Results: There were 149 lower segment caesarean sections accounting to 49.7% and 151 vaginal deliveries including instrumental deliveries which was accounting to 50.3%. Minimum number of coils observed was 2. The maximum number of coils observed was 50. Caesarean section was more in hypo coiling group. APGAR score at 5 min was calculated and there was a total of 109 neonates who had APGAR <7 at 5 minutes (36.33%) out of which there were 17 neonates with hypo coiling (2.33%), 77 neonates with normo-coiling (25.66%) and 15 neonates with hyper coiling (5%). Meconium staining and instrumental delivery was more associated with hyper coiling. Conclusion: Both hyper-coiling and hypo-coiling had significant correlation with adverse perinatal outcome. If the UCI can be measured reliably in utero by ultrasound, then it might be a promising prognostic marker for adverse pregnancy outcome.